Pengaruh Motivation dan Training Terhadap Employee Performance - Rozikin, Nizar; Frianto, Agus (Jurnal Ilmu Manajemen, 2025)
This study is motivated by the importance of motivation and training in improving employee performance in the workplace, particularly in the financial services sector such as PT. Pegadaian Kanwil XII Surabaya. The purpose of this study is to identify and explain the influence of motivation and training on employee performance among the employees of PT. Pegadaian Kanwil XII Surabaya. This research uses a quantitative approach with a population of 50 employees. The sampling technique used is saturated sampling, in which the entire population is used as the sample. The data analysis method employed is multiple linear regression with the help of SPSS version 25 software. The results of the study indicate that motivation has a significant positive effect on employee performance, and training also has a significant positive effect on employee performance. These findings affirm that efforts to enhance motivation through the provision of adequate incentives and workplace facilities, as well as improvements in the quality and accessibility of training, can directly impact the improvement of employee performance. Keywords: employee performance; human resources; motivation, pawnshop, and training